2000
DOI: 10.1007/pl00007086
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of the transdermal application of testosterone gel to the penile skin for the treatment of hypogonadotropic men with erectile dysfunction

Abstract: Androgens influence important central and peripheral mechanisms of the erectile system. The relevance of a moderate decrease of serum testosterone level for erectile dysfunction (ED) has not been clarified so far. The aim of our study was to offer an easy transcutaneous method of androgen application. A previous study on the pharmacokinetic profile of the testosterone gel applied, showed marked elevation of the serum levels of testosterone. In our study, 46 hypogonadal patients with ED and total lack of vagina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…To date, other such studies have been performed on American 1,2,5,7,8,11 and German men. 15 In the United States, the Testosterone Gel Study Group 5,7,8 evaluated 163 American hypogonadal men for up to 42 months; for the first 6 months, the study was a randomized, parallel trial of two doses of TTG and a transdermal patch; this was followed by 36 months of open-label study of TTG. Sexual function improved rapidly with TTG treatment, and changes were maintained throughout the 42-month study period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, other such studies have been performed on American 1,2,5,7,8,11 and German men. 15 In the United States, the Testosterone Gel Study Group 5,7,8 evaluated 163 American hypogonadal men for up to 42 months; for the first 6 months, the study was a randomized, parallel trial of two doses of TTG and a transdermal patch; this was followed by 36 months of open-label study of TTG. Sexual function improved rapidly with TTG treatment, and changes were maintained throughout the 42-month study period.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with placebo, the gel significantly improved spontaneous erections, sexual desire and sexual motivation. In Germany, Schultheiss et al 15 performed a pilot study of 46 hypogonadal men with ED for 6-8 weeks and reported a 32.6% success rate with improved erection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations